Nuisance Algae in Ballast Water Facing International Conventions. Insights from DNA Metabarcoding in Ships Arriving in Bay of Biscay - Alba Ardura (Water, 2020)
Ballast water is one of the main vectors of transport of nuisance species among marine ports. Neither treatment nor interchange completely reduces the risk of ballast water containing DNA from harmful species, being a signal of potential threat. However, although there are some efficient treatments, they are not available on all ships and there might be some technological/economical constrains for their active and routine usage. Understanding what routes lead to a higher risk of contamination is important for designing targeted surveillance. We analysed ballast water from seven ships arriving in Gijon port (south Bay of Biscay, Spain). DNA metabarcoding was employed for identification of exotic species and harmful algae. One ship carried DNA of 20 risk species in the ballast water. Three ships contained DNA of only one risk species, and three ships had none. Seventy two algae species were found, 22.2% are exotic to the Bay of Biscay and 11.1% are catalogued as harmful. The results demonstrated the importance of continuous surveillance of ballast water.